The roles of DNA epigenetics and clinical significance in Chronic Myeloid Leukemia: a review - Keramatinia, Aliasghar; Ahadi, Alireza; Akbari, Mohammad Esmaeil; Mohseny, Maryam; Mosavi Jarahi, Alireza; Bahadori-Monfared, Ayad; Hashemi, Mehrdad; Moradi, Afshin; Mehrvar, Narjes; Kazemi, Elham; Movafagh, Abolfazl (Cellular and Molecular Biology, 2018)
Chronic Myeloid Leukemia (CML) is a myeloproliferative disorder characterized by the genetic translocation t(9;22) (q34;q11.2) encoding for the BCR-ABL fusion oncogene. Growing body of evidence suggests that epigenetic abnormalities are involved in tyrosine kinase resistance in CML, leading to leukemic clone escape and disease propagation. The significant of therapeutic role in chronic myeloid leukemia (CML) depends on both genetic and epigenetic mechanisms. This article focused on the CML and epigenetic and clinical significance. An electronic search of peer-reviewed articles was systematically performed to obtain the relevant literature with the CINAHL, cancer, Google scholar, self-experience and PubMed databases. The keywords included leukemia, cancer, illness, epigenetic. The inclusion criteria for the reviews were that the documents were original quantitative research and published in English. Articles that were not directly relevant to the present objective were excluded. Current progress in molecular biology and bioinformatics offer novel promising experiments namely as next generation sequencing for new development in epigenetic figures characterization and more understanding of the epigenetic mechanisms to be successfully utilized for personalized CML therapy in the next coming years.